Análisis para el desarrollo de una plataforma tipo Uber orientada a servicios domésticos en la ciudad de Babahoyo. - Caisa Tisalema, Marisela Rossana (2023)
In the city of Babahoyo, the sector of informal workers is increasing every year. Within this sector, there is a high percentage of people who are dedicated to offering domestic services, as their main or only source of income. Despite the fact that laws have been passed in the country to protect the domestic server and offer them a fair payment for their work, there are still many people who earn very little compared to the hours worked or who cannot find places to offer their services. On the other hand, people who need to hire domestic services have difficulties finding trustworthy people who meet their needs, which makes them give up on that search. As a solution to this problem, it is proposed to carry out an analysis to develop a digital platform where domestic workers can offer their services, carry out work that is close to their home, and that allows them to see the number of hours worked and earnings obtained. In the same way, the platform will allow requesting users to search for these workers according to their needs and the address where they require the service quickly and safely. Thanks to this analysis, it will be possible to determine if it will be possible to carry out this type of platform that will serve as an intermediary between the applicant and the bidder, it will be possible to facilitate the hiring process and that there are greater offers for domestic workers in the city of Babahoyo, ensuring a fair payment for the work done.